Psychomotor performances relevant for driving under the combined effect of ethanol and synthetic cannabinoids: A systematic review - Giorgetti, Arianna; Orazietti, Vasco; Busardò, Francesco Paolo; Giorgetti, Raffaele (Frontiers in Psychiatry, 2023)
Objective: To determine whether the acute co-consumption of ethanol and synthetic cannabinoids (SCs) increases the risk of a motor vehicle collision and affects the psychomotor performances relevant for driving. Design: Systematic review of the literature. Data sources: Electronic searches were performed in 2 databases, unrestricted by year, with previously set method and criteria. Search, inclusion and data extraction were performed by two blind authors. Results: 20 articles were included, amounting to 31 cases of SCs-ethanol co-consumption. The impairment of psychomotor functions varied widely between studies, ranging from no reported disabilities to severe unconsciousness. Overall, a dose-effect relationship could not be observed. Conclusion: Despite the biases and limitations of the literature studies, it seems likely that the co-consumption poses an increased risk for driving. The drugs might exert a synergistic effect on the central nervous system depression, as well as on aggressiveness and mood alterations. However, more research is needed on the topic.